Hubungan Antara Self-Afficacy Dan Motivasi Berprestasi Pada Atlet Shorinji Kempo Sekolah Keberbakatan Olahraga Flobamorata Kupang - Ndun, Alfaleon Rivael; Nayoan, Christina; Ratu, Feronika; Kiling , Indra Yohanes (Innovative: Journal Of Social Science Research, 2025)
The background of the problem in this study is that SKO NTT athletes are less confident in their potential or in this case have low self-efficacy, which causes their motivation to achieve to decrease. This study aims to determine the relationship between self-efficacy and achievement motivation in Shorinji Kempo athletes at Flobamorata Kupang Sports Excellence High School. Self-afficacy is an individual's belief in their ability to complete tasks and face challenges, while achievement motivation is an internal drive to achieve success and excellence in the field of sports. This study used a quantitative approach. The research sample consisted of 50 athletes, both male and female. The instruments used were the Physical Self-afficacy Scale (PSE) questionnaire to measure self-afficacy and the achievement motivation scale. Data analysis was conducted with linearity test and determination test. The results of the linearity test showed that there was a significant relationship between self-efficacy and achievement motivation (p < 0.001), which means that the relationship between the two is linear. Furthermore, the determination test shows an R square value of 0.758, which means that 75.8% of the achievement motivation variable is influenced by self-efficacy, while the remaining 24.2% is influenced by other factors outside this study. Based on these results, it can be concluded that the higher the self-efficacy of an athlete, the higher the achievement motivation. It is recommended that coaches and schools provide a reward system and conduct regular evaluations of progress and failure as a means of increasing athletes' self-efficacy and achievement motivation.